Wearable Technologies in Team Sports: A Systematic Review of Their Role in Training Load Management and Injury Prevention - Zaluska, Urszula; Szymczyk , Simone; Barczuk, Patryk; Pluta, Natalia; Stobiński, Karol; Marcinkowska, Anna; Lech, Jakub; Płusa, Aleksandra; Kopyt, Weronika; Jóźwiak, Sabina (Quality in Sport, 2026)
The rapid development of wearable technologies has significantly influenced contemporary team sports by enabling advanced athlete monitoring and supporting data-driven training management. The aim of this systematic review was to evaluate the role of wearable technologies in team sports, with particular emphasis on training load monitoring, athlete performance analysis, and injury prevention. A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science, and studies were selected according to predefined inclusion and exclusion criteria. The analyzed literature indicates that wearable technologies, such as global positioning systems (GPS), inertial measurement units (IMU), accelerometers, and heart rate monitors, are widely used to assess both external and internal training load. These systems enable continuous data collection on movement patterns, physiological responses, and biomechanical demands during training and competition. As a result, they support workload evaluation, facilitate individualized training programs, and enhance evidence-based decision-making. Wearable technologies also contribute to injury prevention by enabling monitoring of cumulative load and sudden changes in training intensity, which may indicate increased injury risk. However, limitations remain, including issues related to measurement validity, inter-device variability, and challenges in data interpretation. In conclusion, wearable technologies represent valuable tools for improving athlete monitoring, optimizing training processes, and supporting injury prevention in team sports. Their effectiveness depends on both device accuracy and appropriate data interpretation. Further research is needed to standardize their application across different sports and performance levels.